Preventing Terrorism: A Case Study Of Malaysia - Abdullah, Ahmad Nazzan (2018)
This study is undertaken to examine the preventive methods undertaken by Malaysia in dealing with terrorism. It has become the number one security threat to the nation. As such, it will be probed from its historical perspective, right to the latest preventive approach. Malaysia has the experience of dealing with terrorism from the Communist Emergency period of 1948 to 1960. Subsequently, the methods and approaches were improved and modified to suit the changing times. The research question is, what are the methods undertaken by Malaysia to prevent terrorism. The objective is to find out its effectiveness and the challenges faced in implementing the policies, It is a qualitative study and the methodology used is analyzing, primary data collected by indepth interview, from selected stakeholders, and also secondary data.